Strategi Pemasaran Sosial dalam Meningkatkan Pendapatan Masyarakat pada Bank Sampah Barokah Bersama Kelurahan Mayang Mangurai Kecamatan Alam Barajo - Nurhasanah Nurhasanah; Musnaini Musnaini; Husni Hasbullah; Sigit Indrawijaya (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to find out how social marketing of waste banks increases people's income in the Mayang sub-district, Alam Barajo sub-district. The research method used is a descriptive qualitative approach by collecting data through observation, interviews, observations and documentation. The data sources were obtained through primary and secondary data. This research was conducted to see how social marketing was implemented by the Barokah Bersama waste bank in the Mayang Manguari sub-district, Alam Barajo sub-district and whether there was an increase in income in the implementation of social marketing by the Barokah Bersama waste bank in the Mayang Mangurai sub-district, Alam Barajo sub-district.